The Principal's Strategic Role in Improving the Quality of Learning Through Academic Supervision Activities - Mambaul Musofa; Istikomah Istikomah; Budi Haryanto (International Consortium of Education and Culture Research Studies, 2020)
Quality education is always desired by the community, the quality of education in Indonesia is characterized by the achievement of the National Education Standards (SNP) or exceeding the SNP. One factor that determines the quality of education is the implementation of quality learning as well, quality learning is only produced by qualified teachers. The competency standards that must be possessed by teachers are pedagogic, personality, social and professional competencies. Teacher competency improvement needs to be improved along with the rapid development of science and technology, so that through quality learning can prepare graduates who are ready to face life in their day. To prepare qualified teachers cannot be separated from the principal's role as educator, manager, administrator, supervisor, leader, innovator, and motivator. In Permendikbud 15 of 2018 the Principal's Workload is entirely to carry out tasks: managerial, entrepreneurship development and supervision to Teachers and education staff. One of the principal tasks of the principal is to supervise teachers in order to prepare quality learning. This study wants to discuss the Principal's Strategic Role in Improving Learning Quality through Academic Supervision Activities.